Chemical investigation of metabolites produced by an endophytic fungi Phialemonium curvatum from the leaves of Passiflora edulis. Issue 20 (18th October 2018) - Rathnayake, G. R. Nalin; Kumar, N. Savitri; Jayasinghe, Lalith; Araya, Hiroshi; Fujimoto, Yoshinori
Abstract: Phialemonium curvatum, an endophytic fungus isolated from the leaves of Passiflora edulis was cultured in potato dextrose broth (PDB) media and chromatographic separation of the EtOAc extract of the broth and mycelium led to the isolation of 4-hydroxybenzoic acid (1 ), 3-indole acetic acid (2 ), solaniol (3 ), uracil (4 ), uridine (5 ) and glycerol (6 ). Compound2 showed a weak antifungal activity against Cladosporium cladosporioides . This is the first report of the isolation of the endophytic fungus P. curvatum from P. edulis and complete 13 CNMR assignments of3 . Abstract :